Reakcja krążeniowa na wysiłek statyczny u ludzi trenujących siłowo = Circulatory response to static effort in people doing strength training - Michalski, Cezary; Pilis, Wiesław; Pilis, Anna; Pilis, Karol (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the presented research was to demonstrate the changes in circulatory response in people doing strength training against the background of people who do not train. The study involved 33 people with a 6 years strength training experience (weightlifters, bodybuilders and triathletes) and 10 people at the same age and similar body weight but with no training experience.
Keywords: trening siłowy; skład ciała; układ krążenia; strength training; body composition; circulatory response